Optimization of Tempe Fermentation With the Addition of a Combination of Yeast and Starch Flour: Effect on Process Speed and Product Freshness Period - Cicik Sudaryatiningsih; Yonathan Suryo Pambudi (International Journal of Integrated Science and Technology, 2024)
This research explores the potential for adding a combination of tempeh yeast and starch to the tempeh fermentation process to speed up fermentation and extend the product's freshness period. Through an experimental approach, we investigated the effect of the proportion of yeast and starch on the fermentation speed and shelf life of tempeh. We found that a yeast to starch ratio of 1:2 significantly accelerated the fermentation process, while a ratio of 1:1 was effective in extending the shelf life of tempeh up to 80 hours. Organoleptic tests show positive consumer acceptance of the tempeh variations produced. This research makes a significant contribution to tempeh processing technology, offering practical solutions for the fermented food industry to improve the quality and attractiveness of tempeh products on the market.